Proton-transfer mediated enhancement of nonlocal electronic relaxation processes in X-ray irradiated liquid water - Slavíček, Petr; Winter, Bernd; Cederbaum, Lorenz S; Kryzhevoi, Nikolai V (Journal of the American Chemical Society, 2014)
We have simulated the oxygen 1s Auger-electron spectra of normal and heavy liquid water using ab initio and quantum dynamical methods. The computed spectra are analyzed and compared to recently reported experimental data. The electronic relaxation in liquid water exposed to ionizing X-ray radiation is shown to be far more diverse and complex than anticipated and extremely different than for an isolated water molecule. A core-level ionized water molecule in the liquid phase, in addition to a local Auger process, relaxes through nonlocal energy and charge transfer, such as intermolecular Coulombic decay and electron-transfer mediated decay (ETMD). We evaluate the relative efficiencies for these three classes of relaxation processes. The quantitative estimates for the relative efficiencies of different electronic decay modes help determine yields of various reactive species produced by ionizing X-rays. The ETMD processes which are considered here for the first time in the core-level regime are found to have a surprisingly high efficiency. Importantly, we find that all nonlocal electronic relaxation processes are significantly enhanced by ultrafast proton transfer between the core-ionized water and neighboring molecules.